Under-coordinated atoms induced local strain, quantum trap depression and valence charge polarization at W stepped surfaces - Wang, Yan (2013)
We have explored the effects of atoms under-coordination on surface structure relaxation, binding energy shift of W stepped surfaces and valence charge polarization by the method of incorporating bond order-length-strength (BOLS) correlation mechanism into high-resolution X-ray photoluminescence spectra (XPS) measurements as well as density functional theory (DFT) calculations. Results show that the 4f7/2 energy levels of bulk, surface skin and step edge W atoms shift deeper from 2.17 to 2.69 eV with respect to that of the isolated W (28.91±0.01 eV) atoms, while the valence charge energy shift upper from inner to outer layer and from bulk to stepped edge. The surface bond contraction occurs around under-coordinated atoms after geometry relaxation calculation. Consistency among BOLS calculations, DFT calculation and experimental measurements clarifies that the surface bond contraction and consolidation due to the effects of under-coordination atoms induce potential trap depression, which provides perturbation to the Hamiltonian and hence contributes to the surface core level shift deeper, and that the surface valence charge are polarized by the densely trapped core-level electrons to upper energy.